Pengaruh Media Pembelajaran Daring terhadap Hasil Belajar PWPB Kelas XII RPL SMK N 1 Bukit Sundi - Resti Rahmi Khairati Costa; Latifah Annisa; Ambiyar Ambiyar; Deviana Ridhani (Journal on Education, 2023)
This study aims to determine the effect of online learning (X) on learning outcomes in web programming and mobile devices (Y) subjects at SMK N 1 Bukit Sundi. This study uses quantitative research. The data collection technique uses a questionnaire which is distributed to students. The population in this study were all class XII students majoring in RPL SMK N 1 Bukit Sundi totaling 40 students. The number of samples in this study were 40 students. Data analysis used simple linear regression analysis through calculations with the help of the IBM SPSS Statistics 26 program. The results showed that "The influence of online learning has a positive effect on learning outcomes of PWPB subjects at SMK N 1 Bukit Sundi". Linear Regression Equation The simple linear equation Y = 33.258 + 0.701X is obtained. From the results of the analysis, tcount is 4.284 > ttable value is 2.024 or Ho is rejected. Thus "Online Learning has a positive effect on Learning Outcomes of Class XII RPL PWPB subjects". This can be seen in the coefficient table of the tcount and the p-value is less than 0.05. The coefficient of determination is as big as in the table above, namely the value of R Square = 0.326 = 32.6%, this means that the variation in the learning outcomes variable is PWPB subject.